2005
DOI: 10.1542/peds.2005-0786
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of the Effectiveness of Community-Based Case Management in Insuring Uninsured Latino Children

Abstract: Community-based case managers are more effective than traditional Medicaid/SCHIP outreach and enrollment in insuring uninsured Latino children. Case management may be a useful mechanism to reduce the number of uninsured children, especially among high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 17 publications
0
54
0
Order By: Relevance
“…Other research indicates that community-based case managers and application assistors can increase enrollment, particularly among racial/ethnic minorities and non-English speakers. 19,20 Although the National Survey of CSHCN provides useful information about why low-income uninsured CSHCN are not enrolled in public coverage, it is not without its limitations. Most notably, it has a low uninsured rate when compared with other national surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Other research indicates that community-based case managers and application assistors can increase enrollment, particularly among racial/ethnic minorities and non-English speakers. 19,20 Although the National Survey of CSHCN provides useful information about why low-income uninsured CSHCN are not enrolled in public coverage, it is not without its limitations. Most notably, it has a low uninsured rate when compared with other national surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Prior qualitative research resulted in a taxonomy of 11 domains consisting of 52 barriers to enrollment of eligible uninsured children [8]. A subsequent RCT by our research team demonstrated that community case-management strategies targeting these barriers can lead to uninsured Latino children obtaining and maintaining health insurance coverage [17]. Another RCT by our team documented that PMs can be a highly efficacious and cost-effective mechanism for eliminating racial/ethnic disparities in asthma for minority children [18].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding Eligibility Criterion 4, prior work by the research team has established that phone or in-person follow-up with intervention families is crucial to the success of a community-based intervention to insure uninsured children [17,27]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations